Evaluasi kualitas fisik dan mikrobiologi daging kambing yang dimarinasi dengan jus buah andaliman - Amali, M. Rizky; Sinaga , Kurniawan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
The ain of this research was to determine the effect of using andaliman fruit juice on pH, cooking loss, water holding capacity and microbiology in goat meat.The study used a non-factorial Completely Randomized Design (CRD) with 4 treatments and 5 replications, as well as descriptive methods.The data from the research will be processed statistically using analysis of variance and if there is a significant effect, it will be continued with the Duncan further test. Goat meat has become the main choice among the population because of its good nutritional profile. Data analysis showed that marination with andaliman fruit extract had no significant effect on the pH value, cooking shrinkage, and water binding capacity of goat meat. While microbiology research describes the characteristics of a population or a phenomenon that becomes the object of research that is trial and error. From the observation data analyzed by descriptive method as many as 4 samples of goat meat obtained from the traditional market of kampung lalang, it was found that marinated goat meat with andaliman fruit extract had an effect on P2 with a total of 162 colonies, and increased in P3 with 235 colonies.